Regulating p-block metals in perovskite nanodots for efficient electrocatalytic water oxidation. Issue 1 (December 2017) - Li, Bo-Quan; Xia, Zi-Jing; Zhang, Bingsen; Tang, Cheng; Wang, Hao-Fan; Zhang, Qiang
Abstract Water oxidation represents the core process of many sustainable energy systems, such as fuel cells, rechargeable metal-air batteries, and water splitting. Material surface defects with high-energy hanging bonds possess superb intrinsic reactivity, whose actual performance is limited by the dimension and conductivity of the electrocatalyst. Herein we propose a surface defect-rich perovskite electrocatalyst through ap -block metal regulation concept to achieve high performance for oxygen evolution. As a typicalp -metal, Sn4+ dissolves from the solid phase from model SnNiFe perovskite nanodots, resulting in abundant surface defects with superior water oxidation performance. An oxygen pool model and a fusion-evolution mechanism are therefore proposed for the in-depth understanding ofp -block metal regulation and the oxygen evolution reaction. The energy chemistry unveiled herein provides insights into water oxidation and helps to tackle critical issues in multi-electron oxygen electrocatalysis. Electrocatalysts that possess high densities of surface defects show great promise for efficient water oxidation. Here the authors demonstrate that regulating thep -block metal content in perovskite nanodots imparts these materials with abundant surface defects and excellent electrocatalytic activity.